Severe hypovitaminosis D in pregnant refugees arriving in Europe: neonatal outcomes and importance of prenatal intervention. Issue 1 (10th January 2022) - Liori, Anna; Polychroni, Damaskini; Markantes, Georgios K; Stamou, Maria; Livadas, Sarantis; Mastorakos, George; Georgopoulos, Neoklis
Abstract : Adequate vitamin D levels are particularly important in pregnant women for both maternal and neonatal health. Prior studies have shown a significantly high prevalence of vitamin D deficiency (VDD) among refugees. However, no study has addressed the prevalence of VDD in pregnant refugees and its effects on neonatal health. In this study, we examined the prevalence of VDD in refugee pregnant women living in Greece and compared our results with Greek pregnant inhabitants. VDD was frequent in both groups but was significantly more common in refugees (92.2 vs 67.3% of Greek women, P   = 0.003) with 70.6% of refugees having severe hypovitaminosis D (<10 ng/mL). As a result, most newborns had VDD, which affected refugee newborns to a greater extent. Our results suggest a need to screen newcomer children and pregnant women for VDD in all host countries around the world. Such a screen will appropriately guide early and effective interventions with the goal to prevent adverse neonatal and maternal outcomes.